Clinical application of taTME in reoperative rectal surgery (report of 10 cases) - Tong Weihua; Wang Quan (结直肠肛门外科, 2022)
[Objective] To share the clinical application experience of taTME in reoperative rectal surgery. [Methods] A retrospective analysis was conducted on the clinical data of 10 patients treated between January 2018 and November 2021 in the Department of Gastrointestinal and Colorectal Surgery at the First Hospital of Jilin University. These patients required reoperative rectal surgery due to complications following radical resection of rectal cancer (anastomotic leakage, anastomotic stricture, rectovaginal fistula) or tumor recurrence, and they were treated using taTME. The clinical application of taTME in reoperative rectal surgery was summarized. [Results] Of the 10 patients, 8 who had complications after radical resection of rectal cancer underwent laparoscopically assisted taTME, while 2 patients with tumor recurrence underwent open Beyond-taTME combined total pelvic organ resection. All surgeries were successfully completed, with an operation time of 150-205 minutes, and no ureteral injuries, presacral venous plexus bleeding, or abdominopelvic infections occurred. The patients who experienced complications after radical resection of rectal cancer had their stoma reversed three months post-reoperation. Follow-up showed no anastomotic stricture or obstruction, and rectovaginal fistulas healed well. Patients with tumor recurrence smoothly progressed to postoperative adjuvant treatment. [Conclusion] For a surgical team experienced with taTME, careful selection of suitable cases based on strict surgical indications can yield favorable clinical outcomes in reoperative rectal surgery.